Student-perceived criteria for assessing university relevance in community development - Francis, Joseph; Kilonzo, Beata; Nyamukondiwa, Pertina (South African Journal of Science, 2016)
In sub-Saharan Africa, universities are increasingly being called upon to contribute more towards combating poverty and promoting development in rural areas. Yet, it is still argued that universities are ivory towers, and as a result, their contribution to finding sustainable solutions to issues hampering the realisation of improved quality of life of people in rural areas remains unsatisfactory. This perception emanates from the universities’ apparent failure to articulate and demonstrate how they can achieve the desired goal stated above. Moreover, there are no universally embraced criteria for assessing the relevance of a rural area based university to the community it serves. This study was therefore carried out to determine the perceptions of University of Venda undergraduate students on what they believed were appropriate criteria for assessing the relevance of a rural area based university in community development in South Africa. Reflection circles, anchored on participatory research techniques, were used to engage the students. The results of the engagement were organised into sub-themes. The most prominent perceptions were: ‘A university has active long-term community-based development initiatives’; ‘A university is continuously addressing the real needs of the communities in question’; ‘University initiatives are creating jobs for its graduates and community members’; and ‘Continuous community requests for university assistance in solving the challenges militating against development’. The wide range of perceptions of students observed in this study is a useful input into initiatives seeking to develop an objective tool for assessing the relevance of a rural area based university in community development.Significance: • A set of criteria that students believe should be used to assess the relevance of universities in community development were generated.• The criteria can be used to develop an index that might serve as a tool for ranking university relevance to their constituencies.• The criteria can also be used to sharpen the business of community engagement directorates in ruralbased universities.